2013
DOI: 10.1186/2045-709x-21-40
|View full text |Cite
|
Sign up to set email alerts
|

Do preoperative fear avoidance model factors predict outcomes after lumbar disc herniation surgery? A systematic review

Abstract: BackgroundLumbar disc herniation (LDH) surgery is usually recommended when conservative treatments fail to manage patients’ symptoms. However, many patients undergoing LDH surgery continue to report pain and disability. Preoperative psychological factors have shown to be predictive for postoperative outcomes. Our aim was to systematically review studies that prospectively examined the prognostic value of factors in the Fear Avoidance Model (FAM), including back pain, leg pain, catastrophizing, anxiety, fear-av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…However, they reported that higher baseline disability, as assessed by the ODI, did correlate with surgical outcomes [ 12 ]. Another systematic review reported that patients with high levels of depression, anxiety and fear-avoidance behaviors were more likely to have poor outcomes following LDH surgery [ 13 ]. Still other studies reported that Pfirrmann’s grade [ 14 ], more laterally located discs, extrusion and protrusion herniation types, and larger fragments [ 15 ] could predict the risk of conservative treatment failure in patients with LDH.…”
Section: Discussionmentioning
confidence: 99%
“…However, they reported that higher baseline disability, as assessed by the ODI, did correlate with surgical outcomes [ 12 ]. Another systematic review reported that patients with high levels of depression, anxiety and fear-avoidance behaviors were more likely to have poor outcomes following LDH surgery [ 13 ]. Still other studies reported that Pfirrmann’s grade [ 14 ], more laterally located discs, extrusion and protrusion herniation types, and larger fragments [ 15 ] could predict the risk of conservative treatment failure in patients with LDH.…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern of findings were observed in a review of randomized controlled trials (RCTs) of non-operative pain treatment ( k = 17), such that, among persons with chronic pain for less than 6 months, greater fear-avoidance beliefs at baseline were associated with greater levels of self-reported disability and reduced likelihood of returning to work at 1-month, 6-month, and 1-year follow-ups [17]. Third, the authors of a review of RCTs of surgical intervention for lumbar disc herniation ( k = 4) concluded that high fear-avoidance beliefs at baseline tended to be associated with poor surgical outcomes (i.e., pain, disability, return to work) [18]. Notably, of the two systematic reviews that examined associations between pain-related fear and disability as a function of pain duration [16,17], both observed greater consistency in prospective associations between pain-related fear and disability among persons with pain of shorter duration (i.e., < 3 months and < 6 months, respectively).…”
Section: Associations Between Pain-related Fear and Disabilitymentioning
confidence: 99%
“…These factors can aggregate to increase overall disability leading to greater pain perception, which in turn cycles back to increase pain‐related fear and avoidance. This cycle conceptualizes the Fear Avoidance Model and has been supported in scientific literature .…”
Section: Introductionmentioning
confidence: 99%